Ошибка Джеймса Бонда: повесть / Е. В. Артамонова - Артамонова Елена Вадимовна (Черный котенок, 2011)
Экземпляры: ДБ (20111205) / Инвентарный номер: 40145zzzzz / Цена: 122.00 / Сис.шифр: 84(2) / Авт.знак: А 86 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)